Interactions of genetic and macronutrient intake with abdominal obesity among middle-aged vegetarians in Malaysia - Yuan, Kei Ching; Yit, Siew Chin; Appukutty, Mahenderan; Yoke, Mun Chan; Poh, Ying Lim; Nasir, Khairun Hisam (HEC Press, 2023)
Background and objectives: Evidence for gene-diet interactions is lacking among individuals with specific dietary practices including vegetarians. This study aimed to determine the interactions of rs174547 in the fatty acid desaturase 1 (FADS1) gene with macronutrient such as carbohydrate (particularly fibre), protein and fat intakes on abdominal obesity among middle-aged Malaysian vegetarians of Chinese and Indian ethnicity. Methods and study design: The present cross-sectional study was conducted among 163 vegetarians in Kuala Lumpur and Selangor, Malaysia. Dietary intakes of vegetarians were assessed by using a food frequency questionnaire. Waist circumference of vegetarians was measured by using a Lufkin tape W606PM. Genotypes of the rs174547 of vegetarians were determined by using Agena® assARRAY. A multiple logistic regression model was used to determine the interactions of the rs174547 with macronutrient on abdominal obesity. Results: About 1 in 2 vegetarians (51.5) had abdominal obesity. Individuals with CT and TT genotype at T3 intake of carbohydrates, protein, fat and fibre as well as individuals with TT genotype at T2 intake of carbohydrates and protein had higher odds of abdominal obesity (pinteration <0.05). The gene-diet interaction remained significant for fibre intake (OR: 4.71, 95 CI: 1.25-17.74, pinteraction=0.022) among vegetarians with TT genotype at T2 intake of fibre after adjusting for age and sex and considering the effects of ethnicity and food groups. Conclusions: The rs174547 significantly interacted with fibre intake on abdominal obesity. A specific dietary fibre recommendation based on genetics is needed among Chinese and Indian middle-aged vegetarians.